Nova cabeça robótica com visão estéreo - Nunes, João Felipe Calvo (2010)
This paper presents the implementation of a new robotic head with stereo vision built from a simpler pre-existing version. The methods used in the design and the implementation of the complete system are presented, as well as the results obtained.